Changes in competition as a derivative of changes in business models - Kolomiyets , Ganna; Riabovol, Dmytro (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2024)
The relevance of the topic of this study is determined by the active process of changes that occur in the business environment and cause the development of digital technologies and the emergence of global marketplaces such as Amazon, eBay, and Alibaba. These platforms, on the one hand, have an impact by providing access to the worldwide market for small and medium-sized enterprises. Still, on the other hand, they transform competitive mechanisms and the environment as a whole, creating new challenges for participants in bilateral markets. Traditional business models, despite their relevance, need adaptation and a new theoretical understanding. The purpose of the article is to analyze the impact of global marketplaces on competition and determine the structure of this multi-level interaction mechanism. The object of the study is the interaction between global marketplaces and traditional business models, as well as their impact on the competitive behavior of enterprises in the conditions of the modern digital market. The methodological basis of the research is the analysis of recent scientific articles, empirical studies, and examples that allow us to obtain a general understanding of new market dynamics in modern conditions. The results show that competition in marketplaces has a complex multi-level character. The competitive structure includes macro, meso, and micro levels with technologies dominating each. The integration of digital technologies, process optimization, and the use of big data are key drivers of competitive advantages. The research conducted a general analysis of the structure of competition on global marketplaces such as Amazon, Alibaba, and eBay, which revealed its multi-level nature. Special attention is paid to the influence of digital technologies at various levels. A digital business model was determined and the results were systematized in the form of diagrams and drawings for a better understanding of the structure and dynamics of competition. Changes in business models are explained as derived from changes in competition mechanisms. The practical value of the obtained results lies in the formation of a more systematic understanding of changes in the mechanisms of competitive struggle in modern conditions and transformations of business models based on them. This makes it possible to develop recommendations for businesses at different levels of competition, regarding the implementation of current business practices that meet the modern challenges of digital marketplaces and the nature of interaction with them. The purpose of the article is to analyze the impact of global marketplaces on competition and determine the structure of this multi-level interaction mechanism. The object of the study is the interaction between global marketplaces and traditional business models, as well as their impact on the competitive behavior of enterprises in the conditions of the modern digital market. The methodological basis of the research is the analysis of recent scientific articles, empirical studies, and examples that allow us to obtain a general understanding of new market dynamics in modern conditions. The results show that competition in marketplaces has a complex multi-level character. The competitive structure includes macro, meso, and micro levels with technologies dominating each. The integration of digital technologies, process optimization, and the use of big data are key drivers of competitive advantages. The research conducted a general analysis of the structure of competition on global marketplaces such as Amazon, Alibaba, and eBay, which revealed its multi-level nature. Special attention is paid to the influence of digital technologies at various levels. A digital business model was determined and the results were systematized in the form of diagrams and drawings for a better understanding of the structure and dynamics of competition. Changes in business models are explained as derived from changes in competition mechanisms. The practical value of the obtained results lies in the formation of a more systematic understanding of changes in the mechanisms of competitive struggle in modern conditions and transformations of business models based on them. This makes it possible to develop recommendations for businesses at different levels of competition, regarding the implementation of current business practices that meet the modern challenges of digital marketplaces and the nature of interaction with them.